On the effective viscosity of fresh concrete: A homogenization approach - Nguyen-Sy, Tuan; Nguyen-The, Duong (Vietnam Journal of Mechanics, 2019)
Two new homogenization schemes together with the classical generalized self-consistent scheme (GSC) and its extension are proposed to deal with the effective viscosity of fresh concrete. All these models exploit the composite sphere morphology of suspension made of a viscous fluid and spherical particles. They differ from each other by the ways the extra fluid zone (EFZ) located in between the composite sphere are treated. The comparison with experimental data shows that the GSC provides very good result for a well arranged particle size scale that allows mapping the whole medium by composite spheres of different size scales. However, the GSC cannot be used for a suspension with a non negligible volume of the EFZ. For such a case, extensions of the GSC those take into account the contribution of the EFZ to the overall viscous behavior of the system is necessary to fit with experimental data. Two of them work very well for non-cohesive particles and the other can be employed for suspension with cohesive particles such as the case of fresh cement paste.